Promoting Productive English Skills as a Foreign Language through Interaction Activities with Fifth Grade Students of the I.E. The Playón (2021)
This research work has been carried out with the purpose of analyzing how the implementation of interactive activities can promote the oral and written production in English of fifth grade students in a public institution. During the year of work for this research, observations to a focus group, interviews with teachers, tests and questionnaires to students were used as mechanisms for data collection. At the end of the process, and after analyzing the data, the evidence showed a positive result in the levels of learning and production in the foreign language by the students. This result confirms the importance of strengthening receptive skills as a basis for confidence, exploration and production in the foreign language.